A Genome-Wide RNAi Screen for Enhancers of par Mutants Reveals New Contributors to Early Embryonic Polarity in Caenorhabditis elegans - Morton, Diane G. (Genetics Society of America, 2012)
The par genes of Caenorhabditis elegans are essential for establishment and maintenance of early embryo polarity and their homologs in other organisms are crucial polarity regulators in diverse cell types. Forward genetic screens and simple RNAi depletion screens have identified additional conserved regulators of polarity in C. elegans; genes with redundant functions, however, will be missed by these approaches. To identify such genes, we have performed a genome-wide RNAi screen for enhancers of lethality in conditional par-1 and par-4 mutants. We have identified 18 genes for which depletion is synthetically lethal with par-1 or par-4, or both, but produces little embryo lethality in wild type. Fifteen of the 18 genes identified in our screen are not previously known to function in C. elegans embryo polarity and 11 of them also increase lethality in a par-2 mutant. Among the strongest synthetic lethal genes, polarity defects are more apparent in par-2 early embryos than in par-1 or par-4, except for strd-1(RNAi), which enhances early polarity phenotypes in all three mutants. One strong enhancer of par-1 and par-2 lethality, F25B5.2, corresponds to nop-1, a regulator of actomyosin contractility for which the molecular identity was previously unknown. Other putative polarity enhancers identified in our screen encode cytoskeletal and membrane proteins, kinases, chaperones, and sumoylation and deubiquitylation proteins. Further studies of these genes should give mechanistic insight into pathways regulating establishment and maintenance of cell polarity.